2009
DOI: 10.1158/0008-5472.can-08-4622
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Esophageal Squamous Cell Carcinoma from a High-Risk Population in China

Abstract: Genomic instability plays an important role in most human cancers. To characterize genomic instability in esophageal squamous cell carcinoma (ESCC), we examined loss of heterozygosity (LOH), copy number (CN) loss, CN gain, and gene expression using the Affymetrix GeneChip Human Mapping 500K (n = 30 cases) and Human U133A (n = 17 cases) arrays in ESCC cases from a high-risk region of China. We found that genomic instability measures varied widely among cases and separated them into two groups: a highfrequency i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 35 publications
11
69
1
Order By: Relevance
“…The chromosome 17p region involving the P53 locus also shows a high frequency of allelic loss in esophageal cancer. Studies of the P53 gene in esophageal cancer have shown that LOH and mutations are the leading causes of its inactivation, which is in accordance with the 'two-hit' model of tumorigenesis indicating that P53 is a major tumor suppressor in esophageal cancer (13).…”
Section: Discussionsupporting
confidence: 64%
“…The chromosome 17p region involving the P53 locus also shows a high frequency of allelic loss in esophageal cancer. Studies of the P53 gene in esophageal cancer have shown that LOH and mutations are the leading causes of its inactivation, which is in accordance with the 'two-hit' model of tumorigenesis indicating that P53 is a major tumor suppressor in esophageal cancer (13).…”
Section: Discussionsupporting
confidence: 64%
“…Hu and colleagues have reported that gains of PSCA1, CCND1, CTTN, PPFIA1, and SHANK2 at 11q13 are correlated with increased RNA expression in ESCC (36). Sugimoto and colleagues have indicated that GAL is the target of 11q13 amplification in ESCC (37).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of 3p is one of the most frequent genetic alterations in ESCC detected by comparative genomic hybridization and LOH (5)(6)(7)(8), suggesting the existence of one or more TSGs at frequently deleted regions. In our recent study, single-nucleotide polymorphism (SNP) mass array was applied to investigate LOH on 3p in 100 primary ESCC cases (9).…”
Section: Introductionmentioning
confidence: 99%